Critical green routing synthesis of silver NPs using jasmine flower extract for biological activities and photocatalytical degradation of methylene blue. Issue 1 (February 2021) - Aravind, M.; Ahmad, Awais; Ahmad, Ikram; Amalanathan, M.; Naseem, Khalida; Mary, Sony M. Michael; Parvathiraja, C.; Hussain, Shahid; Algarni, Tahani Saad; Pervaiz, Muhammad; Zuber, Muhammad
Abstract: Herin, we prepared silver NPs using jasmine flower extract. The green synthesis process reports a eco-friendly, nontoxic, cost-effective and simple approach to the synthesis of metal and metal oxide nanoparticles. Extract of jasmine flower acts as capping as well as stabilizing agent. The average crystalline size of the XRD pattern is estimated to be 40 nm. FT-IR (Fourier Transform Infrared) spectra confirm the existence of Ag NPs. The UV-Visible spectrum exhibits an absorption peak of between 380 and 440 nm. Structural analysis for silver nanofibers reveals with SEM and TEM technique. The antimicrobial activity of silver NPs was tested for both grams positive and negative bacteria by Agar well diffusion method. Methylene blue is used as a pollutant dye. Silver nanoparticles result in a maximum degradation efficiency of 78% at the end of 120 min. Graphical Abstract: ga1 Highlights: Novel Facile Synthesis of Ag NPs with Jasmine flower extract for photocatalysis applications. The biological activity of silver NPs was tested against different concentration in microbes. Degradation of methylene blue was experimentally studied with the help of sunlight irradiation technique. Degradation efficiency increases from 21% to 72%, degradation efficiency increases due to irradiation time.